Green Materials Engineering An EPD Symposium in Honor of Sergio Monteiro - Ikhmayies, Shadia; Li, Jian; Vieira, Carlos Mauricio Fontes; Margem (Deceased), Jean Igor; de Oliveira Braga, Fabio (The Minerals, Metals & Materials Series, 2019)
This book is focused on the engineering of green materials, which comprise natural composites, bio-inspired armors, waste-added clay ceramics, lignocellulosic fibers, and biodegradable polymers.